Plasmon-enhanced photocatalytic and antibacterial activity of gold nanoparticles-decorated hematite nanostructures - Alp, Emre; İmamoğlu, Rizvan; Savaci, Umut; Turan, Servet; Kazmanli, M. Kursat; Genc, Aziz; İmamoğlu, Rizvan; Alp, Emre (Elsevier Science Sa, 2021)
Hematite (alpha-Fe2O3) nanoparticles have received significant attention from the researchers due to their favorable and desirable properties in diverse applications. In the present study, single-crystalline hematite pseudo-nanocubes and porous nanorods were synthesized by the hydrothermal route without the usage of any surfactant agents, which were then decorated with gold nanoparticles hidrothermally in an aqueous solution in order to increase the solar energy conversion efficiency. The photocatalytic activities of synthesized nanoparticles were studied against Rhodamine B (RhB) under the illumination of AM 1.5 solar simulator. The excellent photocatalytic efficiency was obtained by changing morphological features of hematite nanostructures, along with the photocatalytic performance enhancement up to 25% thanks to the surface plasmon resonances for the gold nanoparticles-decorated hematite nanostructures. For instance, gold-nanoparticles decorated hematite pseudo-nanocubes almost completely degraded all the RhB after 30 min of illumination. It was also observed that all hematite products, with and without gold decoration, exhibited an impressive antibacterial effect and showed the lethal effect in E.coli. The same nanoparticles being photocatalytically active for organic pollutant degradation and having antibacterial effect may have a good potential for waste water remediation applications. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Hematite Nanostructures; Surface Plasmon Resonance; Photocatalysis; Antibacterial; Water Remediation